2021
DOI: 10.5194/bg-2021-16
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Revised fractional abundances and warm-season temperatures substantially improve brGDGT calibrations in lake sediments

Abstract: Abstract. Distributions of branched glycerol dialkyl glycerol tetraethers (brGDGTs) are frequently employed for reconstructing terrestrial paleotemperatures from lake sediment archives. Although brGDGTs are globally ubiquitous, the microbial producers of these membrane lipids remain unknown, precluding a full understanding of the ways in which environmental parameters control their production and distribution. Here, we advance this understanding in three ways. First, we present 43 new high-latitude lake sites … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…S2). Like other Arctic lake sediment records (Zhao et al, 2021;Thomas et al, 2018;Raberg et al, 2021;Peterse et al, 2014) hexamethyl brGDGTs (IIIa, IIIb, IIIc) dominate the brGDGT assemblages (46%), followed by pentamethyl brGDGTs (IIa, IIb, IIc, 30%), then tetramethyl brGDGTs (Ia, Ib, Ic, 23%) (Fig. S2).…”
Section: Gdgtssupporting
confidence: 71%
“…S2). Like other Arctic lake sediment records (Zhao et al, 2021;Thomas et al, 2018;Raberg et al, 2021;Peterse et al, 2014) hexamethyl brGDGTs (IIIa, IIIb, IIIc) dominate the brGDGT assemblages (46%), followed by pentamethyl brGDGTs (IIa, IIb, IIc, 30%), then tetramethyl brGDGTs (Ia, Ib, Ic, 23%) (Fig. S2).…”
Section: Gdgtssupporting
confidence: 71%
“…A possible explanation for the success of the MAF temperature index is that the activity of brGDGTproducing microbes may be heavily depressed under lake ice and/or in frozen soils (Pearson et al, 2011;Shanahan et al, 2013;Peterse et al, 2014;Cao et al, 2020). However, studies employing sub-seasonal sampling of sediment traps and suspended particulate matter in two mid-latitude lakes have shown that brGDGTs are produced within the water column throughout the year, despite the presence of ice cover (Woltering et al, 2012;Loomis et al, 2014b).…”
Section: Warm-season Temperatures Outperform Matmentioning
confidence: 99%
“…There is increasing evidence that oxygen availability strongly affects lacustrine brGDGT distributions (Colcord et al, 2017;Weber et al, 2018;van Bree et al, 2020;Yao et al, 2020). We therefore tested for calibrations within our dataset with mean and minimum dissolved oxygen concentration (DOmean and DOmin).…”
Section: Dissolved Oxygen and Lake Geometry Calibrationsmentioning
confidence: 99%
See 2 more Smart Citations